1996
DOI: 10.1007/bf00168491
|View full text |Cite
|
Sign up to set email alerts
|

Use of the CO2-laser micropoint micromanipulator for the treatment of laryngomalacia

Abstract: Between September 1989 and June 1994, 21 children (17 boys, 4 girls) with moderate to severe symptoms due to laryngomalacia underwent endoscopic surgery using the CO2-laser micropoint manipulator (shot-by-shot, 0.1 s, super-pulse, 2-3 W power; 280 microns beam; 400 mm working distance). Mean age of the children was 5 months (range, 1-11 months). The procedure was performed under high-frequency jet ventilation and consisted in the resection and/or vaporization of the aryepiglottic folds. This tissue removal cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 10 publications
0
22
0
4
Order By: Relevance
“…Over the last 20 years, endoscopic supraglottoplasty has become the procedure of choice for this condition. According to the literature, supraglottoplasty has a success rate of 70-100% [13,15,16]. Our overall success rate was 87%, the results in children without associated neurologic anomalies being better, with resolution in 96%.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Over the last 20 years, endoscopic supraglottoplasty has become the procedure of choice for this condition. According to the literature, supraglottoplasty has a success rate of 70-100% [13,15,16]. Our overall success rate was 87%, the results in children without associated neurologic anomalies being better, with resolution in 96%.…”
Section: Discussionmentioning
confidence: 62%
“…In our series, the patient with Smith-Magenis syndrome (patient 1) presented with a massively overhanging epiglottis. According to Landry et al [16], this type of laryngomalacia is more often observed in infants with severe forms and this condition seems challenging to treat, epiglottopexy being of limited success [26].…”
Section: Discussionmentioning
confidence: 99%
“…In experienced hands, this technique is almost free of complications, is minimally invasive, and usually allows discharge after 2 days. 11,12 The CO 2 laser has also been used with success and without complications in cases of laryngomalacia, 11 subtotal arytenoidectomy especially in adults, 13 and infantile subglottic hemangioma. 14 In chronic cases, the inflammatory lesion of idiopathic subglottic stenosis responds to corticosteroids, but steroid dependence seems to be the rule.…”
Section: Discussionmentioning
confidence: 99%
“…Der Laser hat sich nach den ersten positiven Berichten [19,41] aufgrund seiner hämostatischen Qualität und seiner Prä-zision in den vergangenen Jahren durchgesezt und kann heute als die Methode der Wahl für die Therapie der schweren Verlaufsform der Laryngomalazie angesehen werden [31,38,39].…”
Section: Mikrochirurgisches Vorgehen Mit Der Vonunclassified
“…Zahlreiche Autoren sehen einen Zusammenhang mit dem gastroösophagealen Reflux (GER) [5,6,24,31,38,39].Ein Reflux wurde zwar bei bis zu 80% der betroffenen Kinder nachgewiesen [6], ohne dass allerdings bisher die kausale Verknüpfung beider Symptome endgültig geklärt ist.So wird der GER einerseits sekundär als Reaktion auf die primäre laryngeale Obstruktion gesehen [5], andererseits wird der GER auch als primäre Pathologie mit sekundärer Schä-digung der supraglottischen Schleimhäu-te aufgefasst [38].…”
Section: Eigene Beobachtungenunclassified